Influence of mitochondrial and nuclear genomic dysfunction on lipid homeostasis in lipidemic diseases - Austin, Robyn Hannah (Stellenbosch : Stellenbosch University, 2026)
Thesis (MSc)--Stellenbosch University, 2026.